2020
DOI: 10.7150/thno.44146
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid promotes metabolic maturation of human Embryonic Stem Cell-derived Cardiomyocytes

Abstract: Cardiomyocytes differentiated from human embryonic stem cells (hESCs) represent a promising cell source for heart repair, disease modeling and drug testing. However, improving the differentiation efficiency and maturation of hESC-derived cardiomyocytes (hESC-CMs) is still a major concern. Retinoic acid (RA) signaling plays multiple roles in heart development. However, the effects of RA on cardiomyocyte differentiation efficiency and maturation are still unknown. Methods: RA was added at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 64 publications
0
27
0
Order By: Relevance
“…Treatment of PSC-CMs with supraphysiologic levels of ATRA (1 μmol/L) during early differentiation (days 2-4, mesoderm stage) increased expression of cardiac markers TNNT2, NKX2.5, and MYH6 by day 10, while treatment with retinoic acid from days 15-20 of differentiation enhanced cardiomyocyte size, increased action potential duration, and increased mitochondrial content and maximal respiration capacity [109]. Duration and dose of retinoic acid appear to be important factors in directing cardiomyocytes toward their desired phenotype, as treatment with 500 nmol/L ATRA from days 3-12 of differentiation leads to specification of an atrial cardiomyocyte phenotype rather than ventricular cardiomyocyte maturation [110].…”
Section: Retinoic Acidmentioning
confidence: 99%
“…Treatment of PSC-CMs with supraphysiologic levels of ATRA (1 μmol/L) during early differentiation (days 2-4, mesoderm stage) increased expression of cardiac markers TNNT2, NKX2.5, and MYH6 by day 10, while treatment with retinoic acid from days 15-20 of differentiation enhanced cardiomyocyte size, increased action potential duration, and increased mitochondrial content and maximal respiration capacity [109]. Duration and dose of retinoic acid appear to be important factors in directing cardiomyocytes toward their desired phenotype, as treatment with 500 nmol/L ATRA from days 3-12 of differentiation leads to specification of an atrial cardiomyocyte phenotype rather than ventricular cardiomyocyte maturation [110].…”
Section: Retinoic Acidmentioning
confidence: 99%
“…Thus, combinatorial approaches might be more efficient and necessary to accurately control the maturation of hPSC-CMs to meet different requirements in disease-modeling and clinical applications. Our recent study has indicated that retinoid acid (RA) treatment could also enhance hPSC-CM maturation (Miao et al, 2020), and in the future the combined treatment is expected to further optimize the protocol for hPSC-CM maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The hESCs at 80% confluence were passaged using 0.5 mM EDTA (Sigma, United States), and 2 µM thiazovivin (Selleck Chemicals, United States) was supplemented for 24 h after cell passage. Cardiomyocyte differentiation was induced in the chemically defined medium CDM3 which is made of RPMI1640 (Thermo Fisher, United States), bovine serum albumin (Sigma-Aldrich, United States) and L-ascorbic acid 2-phosphate (Sigma-Aldrich, United States) as previously described (Miao et al, 2020). Briefly, hESCs at 95% confluence were first cultured in CDM3 supplemented with 5 µM CHIR99021 (Sigma-Aldrich, United States) for 2 days to induce mesoderm differentiation, and the medium was then refreshed with CDM3.…”
Section: Cell Culture and Cardiomyocyte Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…PSC-CMs also more closely resemble embryonic than adult cardiomyocytes [79,80], which has led researchers to seek methods for improving PSC-CM maturity. Treatment with retinoic acid led to increases in hESC-CM yield when added 2-4 days after differentiation was initiated and to improvements in maturity (e.g., increases in surface area, sarcomere length, multinucleation, and mitochondrial copy number) when added after the cells had begun beating [81]; however, retinoic acid also appears to direct cardiomyocyte differentiation toward an atrial-like phenotype and may promote the reentry-like conduction disorders associated with atrial arrhythmia [82]. Cardiac fibroblasts, which are the primary producers of cardiac extracellular matrix (ECM) proteins, also improved maturation when included in cultures of hiPSC-CMs [83], and for engineered heart tissues, efforts to improve PSC-CM maturity have led to the development of techniques that recreate the electromechanical properties of native myocardium.…”
Section: Characterization Of Cardiomyocyte Functional Properties Can Also Include Assessments Of the Cells' Electricalmentioning
confidence: 99%